The Effect Of Transformational Leadership Style And Communication On Performance - Rizky Fauzan (Universitas Syiah Kuala, 2023)
To become the best e-sport team requires optimal performance from its players. The good performance of each individual in the e-sport team is influenced by several factors, including transformational leadership and communication. With transformational leadership, followers feel trust, admiration, loyalty, and respect for leaders, and they are motivated to do more than they expect. Good communication in the organization will affect the performance of members because it all depends on how a person conveys information and one's ability to receive messages. Thus, transformational leadership and communication styles will affect the performance of players on the e-sport team.This study aims to determine the influence of leadership and communication styles on player performance during tournaments on e-sport teams in Pontianak. This research method uses quantitative research. The results showed that transformational leadership and communication have an effect and are positive on player performance.